Fermentasi Limbah Cair Produksi Tempe Terhadap Pertumbuhan Seledri (Apium graveolens L.) - Jafar, Jusmiati; Syam, Asrullah; Utamingsih, Dwi (Jurnal Biotek, 2024)
Copyright©2024 The process of producing tempe produces waste material called waste, which consists of two types: solid and liquid waste. The liquid waste that remains contains numerous organic elements that decompose easily and emit an unpleasant smell. This study was to determine the effect of tempeh liquid waste as an organic liquid fertilizer on the growth of celery (Apium graveolens L). The method used was an experimental method using a completely randomized design (CRD) with a long treatment of tempeh liquid waste fermentation of 3 treatments, namely X0 (control), X1 (2 days of fermentation), and X2 (4 days of fermentation), and 3 replications. The data collection included direct measurements of plant height, number of leaves, and fresh weight, as well as environmental measurements like temperature, humidity, and the pH parameters of tempeh liquid waste. The data obtained were analyzed using analysis of variance (ANOVA). The results showed that X2 treatment (4 days of fermentation) resulted in higher growth of celery plants (stem height, number of leaves, and fresh weight) compared to X0 (dick) and X1 (2 days of fermentation). Practical implications for science from this research include reducing liquid waste, increasing agricultural productivity, developing value-added food products, increasing resource efficiency, and most importantly, it can be an innovation for conducting further research, especially related to liquid waste fermentation and plant growth.